2023
DOI: 10.1038/s12276-023-01129-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactate exacerbates lung damage induced by nanomicroplastic through the gut microbiota–HIF1a/PTBP1 pathway

Lihui Xuan,
Zheng Xu,
Jinhua Luo
et al.

Abstract: Exposure to nanomicroplastics (nano-MPs) can induce lung damage. The gut microbiota is a critical modulator of the gut–lung axis. However, the mechanisms underlying these interactions have not been elucidated. This study explored the role of lactate, a key metabolite of the microbiota, in the development of lung damage induced by nano-MPs (LDMP). After 28 days of exposure to nano-MPs (50–100 nm), mice mainly exhibited damage to the lungs and intestinal mucosa and dysbiosis of the gut microbiota. Lactate accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…We read and had great interest in the article written by Xuan et al 1 . This study revealed that mice exhibited lung and intestinal mucosal damage, gut microbiota dysbiosis, and elevated lactate and N-cadherin levels after 28 days of exposure to nano-microplastics.…”
mentioning
confidence: 99%
“…We read and had great interest in the article written by Xuan et al 1 . This study revealed that mice exhibited lung and intestinal mucosal damage, gut microbiota dysbiosis, and elevated lactate and N-cadherin levels after 28 days of exposure to nano-microplastics.…”
mentioning
confidence: 99%